UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 003 PULAU JAMBU CERENTI KABUPATEN KUANTAN SINGINGI (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2014)
Subjects were fourth graderes at SDN 003 Pulau Jambu by totaling 23 studens ,7boys students and 16 gils students. Data collection instruments in this thesis is the a teacheractivities and students and achievement students. From the results of the research activities ofthe teacher in the learning process in the first cycle with the first meeting of an average of 62,50% and the second meeting improve to 75,00 %. In the second cycle the first meeting 80,00%, andthe second meeting improve 87,50%. The results of the data analysis of student activity in thefirst cycle the first meeting of the two meeting 60.00% and the second meeting improve 70,00%.In the second cycle the first meeting of the two meeting 77,50% and the second meeting improveto 85,00%. Based on the results of the data analysis, the average students achievement beforethe action the point of average 57,60 (category less). After the action in the first cycle with theaverage of 66,08 (category enough). In the second cycle meeting improve with the average of75,43 (category good). Mean that the implementation of learning model Problem BasedInstruction ( PBI ) can improve the students achievement of social studies at fourth graderesSDN 003 Pulau Jambi subdistricts Cerenti Kuantan Singingi.Key words : Model Learning of Problem Based Instruction, Students Achievement